The Effect of Sustainability Report Disclosure on Company Value with Profitability as Moderating Variables in Indonesian Companies Asia Sustainability Reporting Award Recipient Rating - Sukmawanti , Eprila Harmi; Vera Subchanifa, Dian Pujiatma; Surepno, Surepno (El-Qish: Journal of Islamic Economics, 2022)
This study aims to determine the effect of sustainability report disclosure on firm value with profitability as a moderating variable in Indonesian companies receiving the 2019-2021 Asia Sustainability Reporting Rating (ASSRAT) award. In this study, the researcher uses a quantitative approach with a population of Indonesian companies receiving the 2019-2021 Asia Sustainability Reporting Rating (ASSRAT) award. Determination of the sample in this study using purposive sampling technique, in order to obtain 13 of 67 companies. The research period was 3 years, so that 39 samples were obtained. The analytical method used is descriptive statistics, classical assumption test (residual normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test), linear regression analysis test using the MRA method, and hypothesis testing (coefficient of determination test and t test). The results of the study show that the disclosure of sustainability reports does not significantly affect the value of companies in Indonesian companies that receive the Asia Sustainability Reporting Rating (ASSRAT) award in 2019-2021. The results of this study also show that profitability as a moderating variable can strengthen the relationship between sustainability report disclosures and the value of Indonesian companies receiving the 2019-2021 Asia Sustainability Reporting Rating (ASSRAT) award.